Functional Non-coding RNA During Embryonic Myogenesis and Postnatal Muscle Development and Disease - Luo, Hongmei; Lv, Wei; Tong, Qian; Jin, Jianjun; Xu, Zaiyan; Zuo, Bo (Frontiers in Cell and Developmental Biology, 2021)
Skeletal muscle is a highly heterogeneous tissue that plays a crucial role in mammalian metabolism and motion maintenance. Myogenesis is a complex biological process that includes embryonic and postnatal development, which is regulated by specific signaling pathways and transcription factors. Various non-coding RNAs (ncRNAs) account for the majority of total RNA in cells and have an important regulatory role in myogenesis. In this review, we introduced the research progress in miRNAs, circRNAs, and lncRNAs related to embryonic and postnatal muscle development. We mainly focused on ncRNAs that regulate myoblast proliferation, differentiation, and postnatal muscle development through multiple mechanisms. Finally, challenges and future perspectives related to the identification and verification of functional ncRNAs are discussed. The identification and elucidation of ncRNAs related to myogenesis will enrich the myogenic regulatory network, and the effective application of ncRNAs will enhance the function of skeletal muscle.